An Assessment of the Implementation of Integrated Task Focused Adult Education Program in Estie Woreda: Challenges and Opportunities - Alemayehu, Yihunie (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
This study was conducted to assess the implementation of task integrated focused adult education program (ITFAEP) in Estie woreda: South Gondar Zone. The study also sought to assess the challenges face and opportunities for effective implementation of this program. Mixed methods design was employed for the study and both qualitative and quantitative techniques were used. The participants of the study were 6 woreda adult education professionals, 33 cluster school supervisors, 114 ITFAEP facilitators, and 48 adult learners. The sampling technique used to select these participants was comprehensive sampling technique for the first three participants (150 in number). The 48 adult learners were selected first by cluster then by lottery system sampling technique. Questionnaires were used to collect quantitative data while qualitative data were collected through interviews, focus group discussions and document analysis. All selected participants were participated in giving responses to the questionnaire except adult learners. Interviews were held with the 6 woreda adult education professionals and 8 cluster school supervisors. The adult learners were participant for the focus group discussion. The documents of 11 ITFAEP facilitators were analyzed using checklist in the form of yes/no. The responses for interviews and the focus group discussions were tape-recorded and transcribed. The gathered data were analyzed quantitatively (tabulation, percentage and mean) and qualitatively by narration. The result of the study indicated that ITFAEP was not being implemented effectively. It was only in report that the program was effective, but the reality did not show the implementation of the program. Both adult learners and their facilitators had no internal interest and motivation to learn and teach well. Though the participants mentioned some fertile grounds such as the increasing of regular students in the villages of adult learners, the current high attention is given to the program by ministry of education and the supply of textbooks for adult learners, the number and degree of the challenges they mentioned were much more than the opportunities. It is found out that adults’ workload, absence of continuous follow-up and support and lack of adequate training were among the major factors hindering the implementation of the program. Therefore, based on the findings of this study, it is recommended that the board and technical committee at woreda and kebele level should provide further training for facilitators on the way how to teach adults effectively. Well organized awareness creation should be done to enhance the interest and motivation of adults and facilitators. Finally, to minimize and gradually solve the problems encountered in the effective implementation of the program, continuous and extensive orientations and training, in the form of workshops and seminars should be offered to cluster supervisors, school principals, and facilitators. Moreover, all stakeholders of the program should try their best for the realization of the program.